The handbook of stress and health : a guide to research and practice - Cooper, Cary L.; Quick, James C. (Wiley-Blackwell, 2017)
A comprehensive work that brings together and explores state-of-the-art research on the link between stress and health outcomes.-Offers the most authoritative resource available, discussing a range of stress theories as well as theories on preventative stress management and how to enhance well-being -Timely given that stress is linked to seven of the ten leading causes of death in developed nations, yet paradoxically successful adaptation to stress can enable individuals to flourish -Contributors are an international panel of authoritative researchers and practitioners in the various specialty subjects addressed within the work.- Resumé vydavatel